Legislative Referral to the Executive Authority is A Necessity or a Waiver of the Legislative Role - Amer Zghair Mohaisen; Elaf Abdul Rasool Sabri (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The practical and philosophical necessities have highlighted the necessity to increase the legislative role of the executive authority so that the administrative authority has the authority to issue the executive regulations necessary to activate and facilitate the implementation of laws on the ground. This study was divided into two requirements: the first is the legislative referral and its legal basis, and the second is the legislative referral controls. We have recommended that the executive authority, when practicing legislative referral and issue executive regulations, respect the formalities stipulated in the constitution during the exercise of legislative referral, in addition to the obligation to adhere to the general constitutional principles and not deviate from the provisions and principles of the constitution and respect the goal and objectives that it seeks to achieve, otherwise it becomes Its behavior is illegal because it is unconstitutional, whether formally or objectively.